Impact of Social Media Marketing on Purchase Intention and Brand Loyalty: Evidence from Indonesia’s Banking Industry - Laksamana, Patria (International Review of Management and Marketing, 2018)
The purpose of the study is to explore the impact of social media marketing towards purchase intention and brand loyalty. The context of the study was retail banking in Indonesia and a questionnaire was developed with 286 respondents. It has been found that social media marketing leads to purchase intention and brand loyalty. Hence, brand loyalty affected by purchase intention. The implications for marketing managerial and future research are discussed. Keywords: Social media marketing, purchase intention, brand loyalty JEL Classification: M31